Wounded Knights - Thomas, Alfred. author. aut Link
XVI, 256 p. 25 illus., 21 illus. in color.
Keywords: This broad-ranging book draws on Freudian and post-Freudian theory to offer a new and original perspective on courtly love from its origins in eleventh-century Occitania to its transformation into conflicting chivalric and courtly discourses in the later Middle Ages. Comparative and transnational in scope, it explores the role of masculinity and violence in the romance, love lyric and saints’ lives written in French, English, German, and Czech between 1200 and 1400. Whereas conventional studies of medieval courtly love have emphasized the positive and idealistic relationship between the knight and the lady, this book highlights the dark side of medieval masculinity and how displaced male violence toward women and male masochism in these texts are transfigured into more explicit violence in modern horror films. Alfred Thomas is Professor of English at University of Illinois at Chicago, USA. His most recently published books include The Czech Legend of St. Catherine of Alexandria: The Text and its Context (2024), Writing Plague: Language and Violence from the Black Death to COVID-19 (2022), The Court of Richard II and Bohemian Culture: Art and Literature in the Age of Chaucer and the Gawain Poet (2020), Shakespeare, Catholicism, and the Middle Ages: Maimed Rights (2018), and Reading Women in Late Medieval Europe: Anne of Bohemia and Chaucer's Female Audience (2015).